[Rebels without a cause ; A Public affair ; Rhythm of the night [videorecording] - Lazaro, Cheche (The Probe Team, 1990)
Looks into the final report of the Davide Commission. After nearly ten months of investigation into the December 1, 1989 coup attempt, the report cites the causes and give recommendation to the government; why shows like Public Forum, The Weekly TV Public Affairs do not get the support to stay on; Probe Team staffers'disco hopping to see what the night life has to offer and to find out what makes the disco scene the place to be seen.